L’excès dans le premier volume des Juvenilia de Jane Austen - Marie-Laure Massei (Cahiers Victoriens et Edouardiens)
Jane Austen’s juvenile works, written between 1787 and 1793, are framed by the joint themes of excess and exaggeration, which come out in the different plots and styles parodied by the young novelist. By focusing on the 1st volume of the Juvenilia, this paper intends to probe into the various modes and aims of this unexpected aesthetic of excess, while Jane Austen’s mature novels are often praised for their self-restraint and subtlety. Within the grotesque microcosm of these tales, excess and exaggeration are not simply flaws due to the novelist’s youth when she composed them : the recourse to excess enabled Jane Austen to make her own education as a writer, by constantly bordering on parody. Besides, she used this theme as a means of exploring the shortcomings of contemporary sentimental fiction and some conventions in her society.